SMC (Sheet Molding Compound) composite material, preparation method and application of SMC composite material in battery cover of container type energy storage system
By using SMC composite materials, the insulation performance and insufficient corrosion resistance of cast aluminum batteries covered in high external forces and harsh environments have been solved, and battery caps with high compression strength, bending strength and insulation performance have been realized, which improves energy storage. System security and reliability.
Patent Information
- Application Number
- CN202411961864.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing cast aluminum battery covers have a risk of electrical conductivity during use, and the insulation performance and corrosion resistance in high temperature and humid environments are insufficient, which affects the safety and reliability of the energy storage system.
The SMC composite material is used to prepare battery caps with high compression strength, bending strength, insulation performance and corrosion resistance through the carefully designed raw material ratio and preparation process. This material includes resin matrix, enhanced materials, fillers and curing agents, and is prepared through impregnation and roller pressing process.
The stable performance of battery covers in high external forces and harsh environments, avoiding short -circuit risks of electrical, simplified production processes, reducing costs, and improving the overall safety and reliability of the energy storage system.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite materials, and in particular relates to an SMC composite material and a preparation method thereof, and an application thereof in a battery cover of a container-type energy storage system. Background Art
[0002] With the rapid development of renewable energy and the growing demand for electricity, containerized energy storage systems have been widely used in the field of energy storage due to their modularity, scalability and ease of transportation. As an important component of containerized energy storage systems, the performance of battery covers directly affects the safety and reliability of the entire system. At present, the commonly used battery cover products on the market are mainly made of cast aluminum. Although this material has certain strength and durability, it has some obvious shortcomings.
[0003] First, since aluminum is a conductive material, cast aluminum battery covers need to be equipped with additional insulating sheets to prevent electrical short circuits during use, which not only increases the production process and material costs, but may also lead to structural complexity and increased weight. Second, when faced with harsh environments such as high temperature and humidity, the insulation and corrosion resistance of cast aluminum battery covers may be affected, thereby affecting the overall performance and safety of the energy storage system.
[0004] Therefore, it is of great significance to develop a new battery cover material to meet the requirements of containerized energy storage systems for material strength, insulation properties, and corrosion resistance. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an SMC composite material. Through a carefully designed raw material ratio and preparation process, the prepared SMC composite material has high compressive strength and bending strength, ensuring that the battery cover can withstand large external forces and pressures during use; at the same time, it has a high volume resistivity and exhibits good insulation performance. In the process of preparing the battery cover, there is no need to add an insulating sheet, which simplifies the production process and enhances the electrical safety of the system; in addition, the SMC composite material also has good corrosion resistance and can maintain stable performance in harsh environments, thereby extending the service life of the battery cover.
[0006] Another object of the present invention is to provide a method for preparing an SMC composite material and its application in a battery cover of a containerized energy storage system.
[0007] The technical solution adopted by the present invention is as follows: The SMC composite material comprises the following raw materials in parts by weight: Resin matrix: 80-100 parts; Reinforcement material: 35-40 parts; Filler: 35-40 parts; Low shrinkage agent: 10-12 parts; Curing agent: 9-11 parts; Zinc stearate: 1-2 parts; Magnesium oxide: 3-4 parts; Methyl ethyl ketone peroxide: 1-2 parts; The resin matrix includes a mixture of vinyl ester resin, bisphenol A epoxy resin, silicone resin and silane coupling agent; The filler includes glass microspheres and modified Al2O3; the modified Al2O3 is prepared by surface-modifying α-Al2O3 with polystyrene-maleic anhydride copolymer; The low shrinkage agent is polystyrene grafted styrene-butadiene-styrene.
[0008] The resin matrix comprises 35-45 parts of vinyl ester resin, 25-30 parts of bisphenol A epoxy resin, 15-20 parts of organic silicon resin and 3-5 parts of silane coupling agent.
[0009] The vinyl ester resin is DER331, the bisphenol A epoxy resin is E-51, the silicone resin is DC111, and the silane coupling agent is KH550.
[0010] The reinforcing material comprises 25-30 parts of S-2 glass fiber and 7-10 parts of 7628 alkali-free glass cloth.
[0011] The filler is 15-20 parts of glass microspheres and 15-20 parts of modified Al2O3; the particle size of the glass microspheres is 30-150 μm.
[0012] The preparation method of the modified Al2O3 is as follows: α-Al2O3 is added to an acetone solution containing a polystyrene-maleic anhydride copolymer, and after being uniformly dispersed by ultrasonication, the solution is reacted at 50-60°C for 4-6 hours. After the reaction is completed, the modified Al2O3 is obtained by centrifugation, washing and drying; wherein the mass ratio of α-Al2O3 to the polystyrene-maleic anhydride copolymer is 1:(0.5-0.8).
[0013] The preparation method of the polystyrene grafted styrene-butadiene-styrene comprises: dissolving a styrene-butadiene-styrene block copolymer in xylene to obtain a styrene-butadiene-styrene block copolymer solution, then adding benzoyl peroxide to the styrene-butadiene-styrene block copolymer solution, heating the temperature to 70-80°C, adding polystyrene, reacting for 2-4 hours, and after the reaction is completed, distilling off the solvent, and drying to obtain the polystyrene grafted styrene-butadiene-styrene. The amount of the polystyrene is 30-50wt.% of the total amount of the styrene-butadiene-styrene block copolymer, and the amount of the benzoyl peroxide is 0.5-2wt.% of the total amount of the styrene-butadiene-styrene block copolymer.
[0014] The curing agent comprises 6-7 parts of methyltetrahydrophthalic anhydride and 3-4 parts of isophorone diamine.
[0015] The preparation method of the SMC composite material comprises the following steps: (1) Mix the resin matrix evenly, then add the filler, stir evenly, add zinc stearate, magnesium oxide, and methyl ethyl ketone peroxide to the mixture, continue stirring, then add the curing agent, disperse evenly, then add the low shrinkage agent, and stir to obtain a resin mixture; (2) Cut the reinforcement material to a length of 2-3 cm, mix it evenly after cutting, and then use a prepreg machine to evenly impregnate the resin mixture into the cut and mixed reinforcement material to obtain a prepreg; the impregnation time is 10-20 minutes, the temperature is 50-60°C, and the pressure is 0.4-0.6MPa; (3) The prepreg is placed in a mold with PE film on the upper and lower surfaces. After roller compaction and exhaust, it is cured at room temperature for 68-72 hours to obtain an SMC composite material.
[0016] The SMC composite material is used to prepare the battery cover of the container-type energy storage system.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The SMC composite material of the present invention has high compressive strength and bending strength through a carefully designed raw material ratio and preparation process, which ensures that the battery cover prepared by the SMC composite material can withstand large external forces and pressures during use, thereby improving the overall safety and reliability of the energy storage system; (2) The SMC composite material of the present invention adopts a mixed resin matrix of vinyl ester resin, bisphenol A epoxy resin and silicone resin, and fillers such as surface-modified Al2O3. The prepared SMC composite material has high volume resistivity and exhibits good insulation performance. This makes it unnecessary to add an insulating sheet to the battery cover prepared by the SMC composite material during use, thereby simplifying the production process, reducing costs, and improving the electrical safety of the system. (3) The resin matrix and filler in the SMC composite material prepared by the present invention have good corrosion resistance, can maintain stable performance in harsh environments, can extend the service life of the battery cover prepared therefrom, reduce maintenance costs, and improve the overall performance of the energy storage system. DETAILED DESCRIPTION
[0018] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.
[0019] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.
[0020] Some of the raw materials used in the examples and comparative examples are described as follows: Vinyl ester resin DER331: purchased from Dow Chemical, USA; Bisphenol A epoxy resin E-51: purchased from Baling Petrochemical Co., Ltd.; Silicone resin DC111: purchased from Dow Corning, USA; S-2 glass fiber: purchased from AGY Company, USA; 7628 alkali-free glass cloth: purchased from Taijia Chengdu Fiberglass Co., Ltd.; The preparation method of the modified Al2O3 is as follows: α-Al2O3 is added to an acetone solution containing a polystyrene-maleic anhydride copolymer, ultrasonically dispersed for 30 minutes, reacted at 60°C for 5 hours, centrifuged at 4000rpm for 15 minutes after the reaction, removed the supernatant, and washed the solid product obtained by centrifugation with anhydrous ethanol for 3 times, centrifuged to remove the washing liquid after each washing to completely remove the residual acetone and unreacted polystyrene-maleic anhydride copolymer, and placed the washed solid product in an oven at 80°C for 12 hours to obtain the modified Al2O3; wherein the mass ratio of α-Al2O3 to polystyrene-maleic anhydride copolymer is 1: 0.8, and the mass volume ratio of α-Al2O3 to acetone is 1: 5g / mL.
[0021] The low shrinkage agent is polystyrene grafted styrene-butadiene-styrene, and the preparation method thereof is as follows: dissolving styrene-butadiene-styrene block copolymer in xylene, heating to 60°C, and magnetically stirring until completely dissolved to obtain a styrene-butadiene-styrene block copolymer solution; then adding benzoyl peroxide to the styrene-butadiene-styrene block copolymer solution, heating to 75°C, adding polystyrene, and reacting for 3 hours. After the reaction is completed, pouring the solution into a rotary evaporator, heating to 80°C, and removing the xylene solvent by rotary evaporation to obtain a grafted product, and then placing the grafted product in an oven at 60°C and drying for 8 hours to obtain polystyrene grafted styrene-butadiene-styrene; the amount of polystyrene used is 50wt.% of the total amount of the styrene-butadiene-styrene block copolymer, and the amount of benzoyl peroxide used is 1wt.% of the total amount of the styrene-butadiene-styrene block copolymer.
[0022] Example 1 The SMC composite material comprises the following raw materials in parts by weight: Resin matrix: 80 parts; Reinforcement materials: 35 parts; Filler: 35 parts; Low shrinkage agent: 10 parts; Curing agent: 9 parts; Zinc stearate: 1 part; Magnesium oxide: 3 parts; Methyl ethyl ketone peroxide: 1 part; The resin matrix is 36 parts of vinyl ester resin DER331, 26 parts of bisphenol A epoxy resin E-51, 15 parts of silicone resin DC111 and 3 parts of KH550; The reinforcing material is 26 parts of S-2 glass fiber and 9 parts of 7628 alkali-free glass cloth; The filler is 17 parts of glass microspheres and 18 parts of modified Al2O3; the particle size of the glass microspheres is 90±60 μm; The low shrinkage agent is polystyrene grafted with styrene-butadiene-styrene; The curing agent is 6 parts of methyltetrahydrophthalic anhydride and 3 parts of isophorone diamine.
[0023] The preparation method of the SMC composite material comprises the following steps: (1) Mix the resin matrix evenly, then add the filler, stir evenly, add zinc stearate, magnesium oxide, and methyl ethyl ketone peroxide to the mixture, continue stirring, then add the curing agent, disperse evenly, then add the low shrinkage agent, and stir to obtain a resin mixture; (2) Cut the reinforcement material to a length of 2.5±0.5 cm, mix it evenly after cutting, and then use a prepreg machine to evenly impregnate the resin mixture into the cut and mixed reinforcement material to obtain a prepreg; the impregnation time is 15 min, the temperature is 55±5°C, and the pressure is 0.5±0.1MPa; (3) The prepreg is placed in a mold with PE film on the upper and lower surfaces, compacted and exhausted by roller pressing, and then cured at room temperature for 72 hours to obtain an SMC composite material.
[0024] Example 2 The SMC composite material comprises the following raw materials in parts by weight: Resin matrix: 90 parts; Reinforcement materials: 38 parts; Filling: 37 parts; Low shrinkage agent: 11 parts; Curing agent: 10 parts; Zinc stearate: 1.5 parts; Magnesium oxide: 3.5 parts; Methyl ethyl ketone peroxide: 1.5 parts; The resin matrix is 39 parts of vinyl ester resin DER331, 28 parts of bisphenol A epoxy resin E-51, 19 parts of silicone resin DC111 and 4 parts of KH550; The reinforcing material is 29 parts of S-2 glass fiber and 9 parts of 7628 alkali-free glass cloth; The filler is 18 parts of glass microspheres and 19 parts of modified Al2O3; the particle size of the glass microspheres is 90±60 μm; The low shrinkage agent is polystyrene grafted with styrene-butadiene-styrene; The curing agent is 6 parts of methyltetrahydrophthalic anhydride and 4 parts of isophorone diamine.
[0025] The preparation method of the SMC composite material has the same steps as Example 1.
[0026] Example 3 The SMC composite material comprises the following raw materials in parts by weight: Resin matrix: 100 parts; Reinforcement materials: 40 parts; Filling: 40 parts; Low shrinkage agent: 12 parts; Curing agent: 11 parts; Zinc stearate: 2 parts; Magnesium oxide: 4 parts; Methyl ethyl ketone peroxide: 2 parts; The resin matrix is 45 parts of vinyl ester resin DER331, 30 parts of bisphenol A epoxy resin E-51, 20 parts of silicone resin DC111 and 5 parts of KH550; The reinforcing material is 30 parts of S-2 glass fiber and 10 parts of 7628 alkali-free glass cloth; The filler is 20 parts of glass microspheres and 20 parts of modified Al2O3; the particle size of the glass microspheres is 90±60 μm; The low shrinkage agent is polystyrene grafted with styrene-butadiene-styrene; The curing agent is 7 parts of methyltetrahydrophthalic anhydride and 4 parts of isophorone diamine.
[0027] The preparation method of the SMC composite material has the same steps as Example 1.
[0028] Comparative Example 1 The difference from Example 1 is that the organosilicon resin DC111 in the resin matrix is replaced by an equal amount of vinyl ester resin DER331, and the rest is the same as Example 1.
[0029] Comparative Example 2 The difference from Example 1 is that the S-2 glass fiber and 7628 alkali-free glass cloth in the reinforcing material are replaced with an equal amount of E glass fiber, and the rest is the same as Example 1.
[0030] Comparative Example 3 The difference from Example 1 is that the modified Al2O3 is prepared by surface modifying α-Al2O3 with KH570, and the preparation method of the modified Al2O3 is the same as that of Example 1, wherein the mass ratio of α-Al2O3 to KH570 is 1: 0.8, and the rest is the same as that of Example 1.
[0031] Comparative Example 4 The difference from Example 1 is that the low shrinkage agent is an equal amount of styrene-butadiene-styrene block copolymer, and the rest is the same as Example 1.
[0032] The performance tests of the SMC composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were performed respectively, and the test methods were as follows: Compression strength (MPa): Tested in accordance with GB / T 1448-2005; Bending strength (MPa): Tested in accordance with GB / T 1449-2005; Volume resistivity (Ω·cm): Tested in accordance with GB / T 31838.2-2019; Bending strength after acid immersion (MPa): Cut a 50cm×50cm×10cm specimen and immerse it in 50wt.% sulfuric acid at 80℃ for 168h. Then test the bending strength after acid immersion according to GB / T 1449-2005.
[0033] The test results are shown in Table 1.
[0034] Table 1 Performance test results
[0035] As shown in Table 1, the SMC composite materials prepared in Examples 1-3 exhibit good performance in terms of compressive strength, flexural strength and volume resistivity, and good corrosion resistance. With the gradual increase in the content of the resin matrix, reinforcing material and filler, the compressive strength and flexural strength of the composite materials also show an increasing trend.
[0036] In Comparative Example 1, the silicone resin DC111 in the resin matrix is replaced by an equal amount of vinyl ester resin DER331, in Comparative Example 2, the S-2 glass fiber and 7628 alkali-free glass cloth in the reinforcing material are replaced by an equal amount of E glass fiber, in Comparative Example 3, the preparation method of the modified Al2O3 is changed, and in Comparative Example 4, after the low shrinkage agent is replaced by styrene-butadiene-styrene block copolymer, the compressive strength and flexural strength of the prepared composite material are both reduced, and the volume resistivity is also slightly reduced, indicating that the type of resin matrix, the selection of reinforcing material, the modified filler and the type of low shrinkage agent in the present invention all have a significant effect on the mechanical properties, electrical insulation properties and corrosion resistance of the SMC composite material.
Claims
1. A SMC composite material, characterized in that: The invention comprises the following raw materials in parts by weight: Resin matrix: 80-100 parts; Reinforcement material: 35-40 parts; Filler: 35-40 parts; Low shrinkage agent: 10-12 parts; Curing agent: 9-11 parts; Zinc stearate: 1-2 parts; Magnesium oxide: 3-4 parts; Methyl ethyl ketone peroxide: 1-2 parts; The resin matrix includes a mixture of vinyl ester resin, bisphenol A epoxy resin, silicone resin and silane coupling agent; The filler includes glass microspheres and modified Al2O3; the modified Al2O3 is prepared by surface-modifying α-Al2O3 with polystyrene-maleic anhydride copolymer; The low shrinkage agent is polystyrene grafted styrene-butadiene-styrene.
2. The SMC composite material according to claim 1, characterized in that: The resin matrix comprises 35-45 parts of vinyl ester resin, 25-30 parts of bisphenol A epoxy resin, 15-20 parts of organic silicon resin and 3-5 parts of silane coupling agent.
3. The SMC composite material according to claim 2, characterized in that: The vinyl ester resin is DER331, the bisphenol A epoxy resin is E-51, the silicone resin is DC111, and the silane coupling agent is KH550.
4. The SMC composite material according to claim 1, characterized in that: The reinforcing material comprises 25-30 parts of S-2 glass fiber and 7-10 parts of 7628 alkali-free glass cloth.
5. The SMC composite material according to claim 1, characterized in that: The filler is 15-20 parts of glass microspheres and 15-20 parts of modified Al2O3; the particle size of the glass microspheres is 30-150 μm.
6. The SMC composite material according to claim 5, characterized in that: The preparation method of the modified Al2O3 is as follows: α-Al2O3 is added to an acetone solution containing a polystyrene-maleic anhydride copolymer, and after being uniformly dispersed by ultrasonication, the solution is reacted at 50-60°C for 4-6 hours. After the reaction is completed, the modified Al2O3 is obtained by centrifugation, washing and drying; wherein the mass ratio of α-Al2O3 to the polystyrene-maleic anhydride copolymer is 1:(0.5-0.8).
7. The SMC composite material according to claim 1, characterized in that: The preparation method of the polystyrene grafted styrene-butadiene-styrene comprises: dissolving a styrene-butadiene-styrene block copolymer in xylene to obtain a styrene-butadiene-styrene block copolymer solution, then adding benzoyl peroxide to the styrene-butadiene-styrene block copolymer solution, heating the temperature to 70-80°C, adding polystyrene, reacting for 2-4 hours, and after the reaction is completed, distilling off the solvent, and drying to obtain the polystyrene grafted styrene-butadiene-styrene. The amount of the polystyrene is 30-50wt.% of the total amount of the styrene-butadiene-styrene block copolymer, and the amount of the benzoyl peroxide is 0.5-2wt.% of the total amount of the styrene-butadiene-styrene block copolymer.
8. The SMC composite material according to claim 1, characterized in that: The curing agent comprises 6-7 parts of methyltetrahydrophthalic anhydride and 3-4 parts of isophorone diamine.
9. A method for preparing the SMC composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Mix the resin matrix evenly, then add the filler, stir evenly, add zinc stearate, magnesium oxide, and methyl ethyl ketone peroxide to the mixture, continue stirring, then add the curing agent, disperse evenly, then add the low shrinkage agent, and stir to obtain a resin mixture; (2) Cut the reinforcement material to a length of 2-3 cm, mix it evenly after cutting, and then use a prepreg machine to evenly impregnate the resin mixture into the cut and mixed reinforcement material to obtain a prepreg; the impregnation time is 10-20 minutes, the temperature is 50-60°C, and the pressure is 0.4-0.6MPa; (3) The prepreg is placed in a mold with PE film on the upper and lower surfaces. After roller compaction and exhaust, it is cured at room temperature for 68-72 hours to obtain an SMC composite material.
10. An application of the SMC composite material according to any one of claims 1 to 8, characterized in that: Used to prepare battery covers for container-type energy storage systems.
Citation Information
Patent Citations
Unsaturated polyester resin fiber reinforced sheet-shape molding compound and preparation method thereof
CN105482399A
SMC (Sheet Molding Compound) resin with high surface smoothness and preparation method thereof
CN115894810A
Ultra-light high-strength composite material as well as preparation method and application thereof
CN116694030A